THE ROLE OF ENGLISH IN PROMOTING INTERNATIONAL TOURISM - Xojamberdiyeva Niginabonu Sanjarbek kizi (Modern American Journals, 2025)
This annotation examines the role of English in promoting international tourism, highlighting its importance as a global means of communication between tourists and service providers. English enhances accessibility, improves customer satisfaction, and facilitates cross-cultural understanding, making travel experiences smoother and more enjoyable. It also plays a significant role in destination marketing, digital tourism platforms, hospitality services, and tourism education. As a result, English functions not only as a communication tool but also as a strategic factor that strengthens global tourism development and increases international competitiveness.
Keywords: English language, international tourism, global communication, destination marketing, hospitality industry, tourist satisfaction, digital tourism, cross-cultural communication